Analysis of Development Strategy of Lasem Batik Small Industry in Rembang (Case Study in Lasem District) - Iqlima Fauzia; Rusdarti Rusdarti; Dyah Maya Niahayah (Economics Development Analysis Journal, 2017)
Batik Lasem Small Industry in Lasem District, Rembang Regency is one of the leading industries in Rembang Regency. The existence of Batik Lasem small industry makes a great contribution to Rembang’s income. The problem faced is that the number of demand value is lower than the production value of Batik Lasem, so it shows imbalance in the number of demand of Batik Lasem in Rembang Regency. The purpose of this research is describing the profile of Batik Lasem’s entrepreneurs and explaining the internal factors like strength and weakness and also the external factors like opportunity and threat for Batik Lasem small industry in Rembang Regency. The population of this research is 38 entrepreneurs of Batik Lasem small industry in Lasem District, Rembang Regency. The population is taken by using the survey technique. The method of data analysis is descriptive analysis and SWOT analysis. The development strategies of Batik Lasem small industry in Rembang Regency are as follows: the entrepreneurs can enlarge the market share, provide more facilities to the employers in accordance with the needs of production, and also give the training to the entrepreneurs and employers about technology development.